PENERAPAN MANAJEMEN KEPALA SEKOLAH TERHADAP PENERAPAN METODE KOOPERATIF MODEL GROUP INVESTIGATION SEBAGAI ALTERNATIF MENINGKATKAN KINERJA GURU MENGAJAR DI SDN INPRES MANDOK: SDN IMPRES MANDOK, KECAMATAN BULAGI UTARA, KABUPATEN BANGGAI KEPULAUAN - HIRENTO SOILO (Mitra Pendidikan, 2022)
By taking into account the formulation of the problem above, the objectives of this study are 1). Want to know the improvement of teacher performance after the implementation of the Group Investigation model of cooperative learning at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency 2). Want to know the effect of student learning motivation after applying the Group Investigation model of cooperative learning at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency The type of research used by the author in this research is school action research. According to Arikunto (Suyadi, 2012), PTS is a combination of understanding from the words "research, action and school". Research is the activity of observing an object, using certain methodological rules to obtain useful data for researchers and other people for the common good. Furthermore, action is a treatment that is intentionally applied to objects with certain objectives which in their application are arranged into several periods or cycles. And school is a place where a group of students learn together from the same teacher in the same period. The method used in this PTS is using the method developed by Riel (2007) which divides the action research process from each cycle into stages. : (1) planning; (2) implementation of actions; (3) data collection and analysis or in other methods known as the observation stage; and (4) reflection This school action research was carried out at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency for three months, from January to March 2021. In this study, the subjects of the study were the fifth and sixth grade teachers of SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency. even semester of the 2020/2021 school year This school action research instrument consists of 1) Syllabus, 2), lesson plan (RPP), 3). Student Activity Sheet (LKS) 4). Teaching and Learning Activity Observation Sheet. 5). Formative Test. The method of gathering power in this research is through the observation of processing cooperative learning methods with the Group Investigation model, observing student and teacher activities, student motivation questionnaires, and formative tests. Data analysis techniques In this study using qualitative descriptive analysis techniques, which are research methods that describe reality or facts in accordance with the data obtained with the aim of knowing the teacher's performance achieved by students as well as to obtain student responses to learning activities and student activities during the learning process. . From the results of the learning activities that have been carried out, and based on all the discussions and analyzes that have been carried out, it can be concluded as follows 1). Cooperative learning with the Group Investigation model has a positive impact on improving teacher performance at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency 2). The application of the Group Investigation model of cooperative learning has a positive influence, namely it can increase student motivation at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency.